Pengaruh Model Pembelajaran Team Games Tournament terhadap Kemampuan Berfikir Kritis dan Motivasi Belajar IPS Siswa Kelas VII di MTSN 1 Nganjuk - Dhea Salsabil Labibah; Hendra Pratama (Universitas 45 Surabaya, 2024)
This study aims to examine the effect of the Team Games Tournament (TGT) learning model on critical thinking skills and learning motivation in social studies (IPS) among seventh-grade students at MTsN 1 Nganjuk. The problem identified is the low level of students' critical thinking and learning motivation, as reflected in their lack of response to teacher questions and low enthusiasm for social studies. The research used a quantitative approach with a Quasi-Experimental design, dividing students into a control group (conventional learning) and an experimental group (TGT model). The results showed that the application of TGT significantly improved students' critical thinking skills and learning motivation compared to conventional methods. Hypothesis testing confirmed a positive effect, with a significance value of < 0.05.